Allele frequencies of F13A01, FESFPS and vWA STRs in random Tamil population of Malaysia - Velayutham, Sumathy d/o (Allele frequencies of F13A01, FESFPS and vWA STRs in random Tamil population of Malaysia, 2004)
Short tandem repeat (STR) loci are characterized by high levels of length polymorphism within and among populations and they are ideal markers for forensic analysis of biospecimens. In this research project, allele frequencies for three STRs loci that are Fl3A01, FESFPS and vWA in random Tamil population were studied. Buccal swabs were collected from 100 unrelated individuals of ethnic Tamil population of Malaysia. STR profiling of the deoxyribonucleic acid (DNA) extracted from these samples were profiled for the three STR.s using multiplex primer kit (Promega Corporation, USA). Statistical analysis was also carried out to obtain some parameters and comparative studies were carried out with other populations. A database for random Tamil population will help in human identity testing in Malaysia. The genotype frequency distributions do not deviate from the Hardy-Weinberg expectations.